Analysis of the influence of homozygosis of alleles HLA on the waiting time for kidney transplantation (Research, Society and Development, 2021)
The aim of the study was to evaluate whether the homozygosity of the HLA System alleles presented by transplant recipients in Ceará influenced the waiting time for kidney transplantation. This is a cross-sectional study, carried out based on the active search for medical records, of patients who transplanted with a kidney from a deceased donor in the state of Ceará, from January 2018 to December 2019. Data analysis was performed with 406 patients, 84 were excluded. The mean age and waiting time of 47 ± 13.1 years and 14.64 ± 16.18 months, respectively, were observed. Most patients were male (62.3%) with a mean age greater than women (p=0.0034). The average waiting time was higher in the group of patients who were between 36 and 45 years old (p=0.002) when compared to the other age groups, while the waiting time was higher in group O and group A (p=0.001). There was no influence of homozygosity (p=0.934), number of homozygosis (p=0.448) and presence of homozygosis in different HLA loci (locus A, p=0.169, locus B, p=0.629 and locus DR, p=0.064) on the waiting time. Thus, homozygosity in the different alleles of the HLA system did not influence the waiting time on the list of patients who transplanted in 2018 and 2019.  Studies are necessary to better assess the influence of HLA homozygosity in a larger number of receptors, especially in the DR locus. These results will be important to review the selection criteria for potential kidney receptors, since homozygosis is currently not scored.